2023
DOI: 10.1242/jeb.245263
|View full text |Cite
|
Sign up to set email alerts
|

An ultrasound-absorbing inflorescence zone enhances echo-acoustic contrast of bat-pollinated cactus flowers

Abstract: Flowering plants have evolved an extraordinary variety of signaling traits to attract their pollinators. Most flowers rely on visual and chemical signals, but some bat-pollinated plants have evolved passive acoustic floral signals. All known acoustic flower signals rely on the same principle of increased sonar reflectivity. Here we describe a novel mechanism that relies on increased absorption of the area surrounding the flower. In a bat-pollinated cactus (Espostoa frutescens) we found a hairy inflorescence zo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…However, it is also clear that acoustic camouflage works better for higher frequencies, but if this is adaptive or just a physical consequence of a hairy surface still has to be tested. In a study on the reflectance of a hairy inflorescence zone of a bat‐pollinated cactus, it also turned out that absorption worked better for higher frequencies (Simon, Matt, et al., 2023).…”
Section: Discussionmentioning
confidence: 99%
“…However, it is also clear that acoustic camouflage works better for higher frequencies, but if this is adaptive or just a physical consequence of a hairy surface still has to be tested. In a study on the reflectance of a hairy inflorescence zone of a bat‐pollinated cactus, it also turned out that absorption worked better for higher frequencies (Simon, Matt, et al., 2023).…”
Section: Discussionmentioning
confidence: 99%
“…The cephalium is a feature that enhances the location of flowers by bats through the principle of increased ultrasound absorption of the area surrounding the flower, making it more conspicuous (Simon et al . 2023), but also for its orientation that can guide bats during foraging (Albuquerque‐Lima et al . 2023c,d).…”
Section: Discussionmentioning
confidence: 99%
“…The flowers of C. goebelianus are produced in the modified region called a cephalium, a fertile structure composed of densely packed bristle-bearing areoles which, in elongated cacti, is lateral, terminal or in rings, being the region from which the flowers and, later, the fruits emerge (Buxbaum 1953;Mauseth 2006). The cephalium is a feature that enhances the location of flowers by bats through the principle of increased ultrasound absorption of the area surrounding the flower, making it more conspicuous (Simon et al 2023), but also for its orientation that can guide bats during foraging (Albuquerque-Lima et al 2023c, d). Furthermore, it is important to highlight that in the Caatinga areas, a large proportion of C. goebelianus individuals are taller than the surrounding vegetation (Taylor & Zappi 2004), which may contribute to echolocation, as these cacti could be visualacoustic echo beacons that can be easily found without scent.…”
Section: Scentless Coleocephalocereus Flowersmentioning
confidence: 99%
“…Cephalia are believed to fulfill various functions: they certainly protect the developing flowers and fruits from predators, dehydration, excessive heat and/or cold; their bristly or woolly surface also acts as a safe landing platform or hovering space for pollinators, such as diurnal hummingbirds and nocturnal bats, protecting these from the plant's dangerous armament of spines (von Helversen, 1993). It has been suggested that cephalia provide an adequate surface for bat echolocation, thereby orienting visitors toward floral rewards (Simon et al, 2023).…”
Section: Figurementioning
confidence: 99%
“…Whereas polarized light and the magnetic field can explain the movement and orientation of bats during the early part of their foraging routine and explain the overall trend in cephalium orientation, other signals may be of importance to locate flowers at close range, such as echolocation (Simon et al, 2023; Stilz & Schnitzler, 2012); and floral scent and light itself may still be important for the pollinators to locate the flowers at close range (Domingos‐Melo et al, 2021; Gonzalez‐Terrazas et al, 2016). In the case of echolocation, the study by Simon et al (2023), highlighted the important role of the cephalium as a structure that absorbs sound, consequently increasing the echo‐acoustic contrast of the flower compared to the vegetative part. In the case of olfactory cues, the study by Gonzalez‐Terrazas et al (2016) shows that bats use floral scents coupled with echolocation, which allows bats to feed more efficiently, being mainly useful in dark conditions.…”
Section: Figurementioning
confidence: 99%